The role of financial inclusion in mitigating the risks of bank liquidity an applied study of the Iraqi banking sector for the period (2015-2021) - Alothman, هشام عبد الخضر سكر; Al-Sabghani, قاسم كريم جعيل (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research aims to discuss the role of financial inclusion in mitigating banking liquidity risks as well as enhancing access to financial services by enhancing financial inclusion and expanding access to banking and financial services, as individuals and companies can obtain deposit services, loans and other services that help in achieving financial stability. In addition to stimulating economic growth by increasing access to financial services, the research sample included the Iraqi banking sector for the period (2015-2021), and to analyze and test the research hypotheses, multiple linear regression and the method of least squares were used to measure the relationship and impact and by using the statistical program (Eviews.10), The research resulted in a set of conclusions, the most important of which is that the research concluded that the role of financial inclusion lies in providing equal opportunities for everyone to access financial services, and thus contributes to reducing the severity of banking liquidity risks and improving the stability of the banking system. Providing financial services based on technology, as financial inclusion contributes to the development of innovative financial services that use technology, such as banking applications through smart phones and online payment solutions. This provides more efficient and convenient means of accessing banking services and managing liquidity effectively.